2003
DOI: 10.1111/j.1432-2277.2003.tb00299.x
|View full text |Cite
|
Sign up to set email alerts
|

Living-donor liver transplantation for homozygous familial hypercholesterolemia from a donor with heterozygous hypercholesterolemia

Abstract: Familial hypercholesterolemia is a rare inherited disease with an incidence of approximately one per million. Severe hypercholesterolemia is observed from the time of birth onwards. It is associated with severe atherosclerosis in childhood, leading to death from myocardial infarction before the age of 20 years. Liver transplantation is the only effective treatment for this disease. We experienced the case of an infant aged 2 years 5 months who had homozygous familial hypercholesterolemia and who received a liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Recently, mutations in the alleles of three other genes were identified as causal in some cases with a severe phenotype resembling HoFH (1,2). Individuals with FH are at an increased risk of developing premature coronary vascular disease (1)(2)(3)(4)(5)(6)(7)(8)(9). Early detection and proper management of the patients will delay and prevent these lethal complications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, mutations in the alleles of three other genes were identified as causal in some cases with a severe phenotype resembling HoFH (1,2). Individuals with FH are at an increased risk of developing premature coronary vascular disease (1)(2)(3)(4)(5)(6)(7)(8)(9). Early detection and proper management of the patients will delay and prevent these lethal complications.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of these treatments, some patients with severe HeFH, and most cases of HoFH, will not reach optimal LDL-C levels. Thus, some other modalities should be performed including LDL aphaeresis, portocaval shunting, ileal bypass surgery, and liver transplantation (1)(2)(3)(4)(5)(6)(7)(8)(9). Besides liver transplantation, other methods are only partially and transiently successful in reducing cholesterol levels in patients with HoFH, so liver transplantation is currently the most effective and definitive means of treatment in patients with HoFH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liver transplantation was first described in 1983 and has now emerged as the most effective treatment, markedly improving LDL-C levels long term [46, 47]. Surgery provides a liver with functional LDLRs, thereby correcting the molecular defect.…”
Section: Treatmentmentioning
confidence: 99%
“…Prior to 2011, there were six reported cases of preemptive liver transplantation for HoFH performed for their presumed high risk for cardiovascular complications (2)(3)(4)(5). However, in a paradigm shift, in 2011, Maiorana et al reported the case of a seven-yr-old patient with HoFH who underwent preemptive liver transplantation.…”
mentioning
confidence: 99%